Genome-wide association studies identify an association of transferrin binding protein B variation and invasive serogroup Y meningococcal disease in older adults - Maynard-Smith, L; Derrick, JP; Borrow, R; Lucidarme, J; Maiden, MCJ; Heyderman, RS; Harrison, OB (Oxford University Press, 2022)
Background. Neisseria meningitidis serogroup Y, especially ST-23 clonal complex (Y:cc23), represents a larger proportion of invasive meningococcal disease (IMD) in older adults compared to younger individuals. This study explored the meningococcal genetic variation underlying this association.